2014
DOI: 10.1007/s10826-014-0036-z
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Attachment and Children’s Quality of Life: The Mediating Role of Self-compassion and Parenting Stress

Abstract: The stress parents feel in their parenting roles and the ways they relate to themselves in difficult or distressing situations, such as with self-compassion, are influenced by their attachment orientations and may account for the well-known association between the quality of parents' attachment to their own parents and their children's developmental outcomes. We explored the association between self-compassion and parenting stress and their mediating role in the link between mothers' attachment orientations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 48 publications
3
47
0
1
Order By: Relevance
“…As hypothesised, and in support of previous research, attachment was significantly associated with both parenting variables (Rholes et al, 2006;Vieira et al, 2012). In the case of attachment anxiety, an overactivation of the attachment system may lead to unrealistic expectations of the parent-child relationship and elevation of stress levels when the child is perceived as demanding care (Moreira et al, 2015). Conversely, attachment avoidance may generate parental stress due to the difficulties experienced having a dependent child, which is at odds to the desire for self-sufficiency and independence .…”
Section: Discussionsupporting
confidence: 80%
“…As hypothesised, and in support of previous research, attachment was significantly associated with both parenting variables (Rholes et al, 2006;Vieira et al, 2012). In the case of attachment anxiety, an overactivation of the attachment system may lead to unrealistic expectations of the parent-child relationship and elevation of stress levels when the child is perceived as demanding care (Moreira et al, 2015). Conversely, attachment avoidance may generate parental stress due to the difficulties experienced having a dependent child, which is at odds to the desire for self-sufficiency and independence .…”
Section: Discussionsupporting
confidence: 80%
“…However, one study has examined the link between self-compassion and general parenting stress in parents of nondisabled children. Moreira et al (2014) found that self-compassion was negatively linked to parenting stress and that parenting stress mediated the positive association found between self-compassion and child well-being. Also, a few studies with a focus on mindfulness among parents of disabled children have included self-compassion as an outcome variable.…”
Section: Introductionmentioning
confidence: 88%
“…Conversely, parents’ insecurity (anxious and avoidant attachments) is associated with more negative parental caregiving behaviours, emotions, and cognitions. It has been suggested that because avoidant individuals have more difficulty in assuming caregiving roles (George & Solomon, ; Gillath, Shaver, & Mikulincer, ; Rholes, Simpson, & Friedman, ), they tend to feel more uncertainty about (Rholes, Simpson, & Blakely, ) or less desire to have children (Rholes, Simpson, Blakely, Lanigan, & Allen, ; Rholes et al ., ), lack confidence about their parenting abilities (Rholes et al ., ), experience more stress in their parenting roles (Moreira, Gouveia, Carona, Silva, & Canavarro, ; Rholes et al ., ), feel that parenthood is less meaningful and satisfying (Rholes et al ., ) and behave in a less warm, close, and supportive manner towards their children (Edelstein et al ., ; Rholes et al ., ). On the other hand, anxiously attached individuals tend to be more self‐centred and to worry about their own attachment needs (Mikulincer & Shaver, ) as well as to feel extremely distressed when other people need their assistance (Mikulincer, Shaver, Gillath, & Nitzberg, ), which likely interferes with the provision of sensitive care to their children.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, anxiously attached individuals tend to be more self‐centred and to worry about their own attachment needs (Mikulincer & Shaver, ) as well as to feel extremely distressed when other people need their assistance (Mikulincer, Shaver, Gillath, & Nitzberg, ), which likely interferes with the provision of sensitive care to their children. Some studies have found that anxious parents may also be less close to their children (Rholes et al ., ), experience parenting stress (Moreira, Gouveia, et al ., ), have more hostile behaviours towards their child (Jones & Cassidy, ) and endorse more negative attitudes towards parenthood than securely attached parents (Rholes et al ., ).…”
Section: Introductionmentioning
confidence: 99%